Innovative Approaches Using ICT to Support Teaching and Learning Advanced Mathematics - Oldknow, Adrian; Tetlow, Linda (Institute for Mathematical Research, 2009)
The UK has seen a worrying decline in the number of students taking up Higher Education courses in both Mathematics and ICT. The opportunity exists within an A-level mathematics course for teachers and students to use technology in an imaginative way to enhance the learning experience and to encourage students to consider further study in either discipline.Students taking A-level are taught in a variety of institutions. An A-level mathematics class in an 11-18 school could be a small cohesive group with similar background, prior learning experiences and familiarity with the use of ICT in mathematics. A class in a Further Education college is likely to be much larger and to include students from a wide range of previous institutions whose experiences both with regards to teaching and learning styles and to their use of ICT could vary widely.Catering for the individual teacher and student in these diverse circumstances can be a big deterrent to the use of technology, so in the ICTAM (Interactive Companion to Advanced Mathematics) project [3] the authors have put together a unique collection of software which has been designed to offer something to every A-level mathematics teacher and student, whatever their background institution or technological expertise.The paper considers a range of activities from ICTAM which includes:- • Activities based on files for a wide range of powerful mathematics software. • Its own graphing software Java applet, TIM, which teachers ·can adapt. • Dynamic activities based on real world problems and images • Ideas for different teaching approaches. • Supporting instructions and video demonstrations for student/teacher self-help. • Extension challenges for able students.